Acetylenic Indole‐Encapsulated Schiff Bases: Synthesis, In Silico Studies as Potent Antimicrobial Agents, Cytotoxic Evaluation and Synergistic Effects. Issue 8 (27th February 2018) - Singh, Gurjaspreet; Kalra, Pooja; Arora, Aanchal; Singh, Akshpreet; Sharma, Geetika; Sanchita,; Maurya, Indresh Kumar; Dutta, Sanjay; Munshi, Parthapratim; Verma, Vikas
Abstract: A family of pharmacophore acetylenic indole‐3‐carboxaldehyde (3) and acetylenic indole schiff bases (5 a‐5 i) bearing indole framework were synthesized to afford structurally diverse moieties. Acetylenic indole‐3‐carboxaldehyde was coupled with various amines to furnish the novel scaffolds5 a‐5 i . These acetylenic indole Schiff bases (AISB) were synthesized in shorter times under microwave irradiation in comparison to classical reaction conditions. AISB were experimentally characterized by using IR, 1 H NMR, 13 C NMR, X ray crystallographic and mass spectrometric methods. The synthesized compounds showed promising anti‐bacterial and anti‐fungal properties when tested in vitro against six bacterial and seven fungal strains. Among these, hybrids5 a, 5 c, 5 e and5 g were found to be even more potent than the standard drugs and were more influential against the bacterial than the fungal strains. These more potent compounds were then evaluated for their cytotoxicity by MTT assay on Hek293 and HeLa cells. The synergistic effect of bis‐acetylenic compound5 g with kanamycin and amphotericin B has also been scrutinized. Further, the structural and electronic properties of the molecules were investigated theoretically by performing density functional theory (DFT). Abstract : Schiff base encapsulated acetylenic indole were synthesized and well characterized followed by computational evaluation of the compounds. Acetylenic indole Schiff bases (AISB) were synthesized in shorter times under microwave irradiation in comparison to classical reaction conditions. All the synthesized compounds were then evaluated for their antibacterial and antifungal activities. Compounds exhibited excellent antibacterial potency. Compounds with good bioactivity were then evaluated for their cytotoxicity by MTT assay on Hek293 and HeLa cells.